SELECTIVITY OF Decapterus macarelus (SCAD) DRIFT GILLNET IN KAYELI BAY MALUKU BY KITAHARA’S METHOD - Agus Tupamahu (JOURNAL OF COASTAL DEVELOPMENT, 2009)
To study the gear selectivity on scad Decapterus macarelus fishing experiments using drift gill net withdifferents mesh sizes were conducted in Kayeli Bay Buru Island Maluku. To obtain data of fork length sizecomposition, drift gillnets were operated at fish agregation devices along night time. The selectivity of driftgillnets for scad were estimated with Kitahara’s method. Mesh selectivity by a drift gillnet used for scadDecapterus macarelus shows a peaked curved with the efficiency at the peak of mesh selectivity increasingin proportion to the mesh size. The optimum size selectivity (fishing efficiency) of scad are ratio of 185 mmfork length class and 38 mm mesh size, 225 mm and 45 mm mesh size, and 255 mm and 51 mm mesh size.